Developing the City-Level Climate Change Master Plan: The Case of Energy Sector in Bangkok - Wongkot Wongsapai (2018)
© The Authors, published by EDP Sciences, 2016. This study focuses in the developing energy sector plan of city-level climate change master plan in Bangkok, the capital city of Thailand. The energy consumption, which consists of electricity and fossil fuels, are investigated and forecasted to be Business-as-Usual (BaU) scenario covering year 2013 to 2023 by using trend analysis. The Greenhouse Gas (GHG) emission mitigation scenario was then analyzed by applying the energy reduction from the national energy efficiency development plan as well as the own reduction activities by Bangkok Metropolitan Administration (BMA). We can conclude that if the national energy efficiency plan can fully implemented, the GHG reduction potential of the city from energy sector would be at around 18% from BAU in 2023 from all energy conservation and renewable energy measures.